Resource recovery from paddy field using plant microbial fuel cell. (December 2020) - V, Kiran Kumar; K., Man mohan; P Manangath, Sreelakshmi; P, Manju; S., Gajalakshmi
Graphical abstract: Highlights: Plant-MFCs were integrated with paddy field to recover "Nutrients, Energy, & Water". Terracotta cylinders were used as chassis and proton exchange membrane of PMFCs. PMFC performance, catholyte recovery, and paddy growth are found to be correlated. Nutrients like ammonium and clay minerals were recovered throughout the experiment. Abstract: The plant microbial fuel cell (PMFC) is a recently developed energy-generating technology that supports sustainable agriculture. Design configuration is the key bottleneck in optimization and upscaling of paddy based PMFCs. In this study, two designs (Type-I (horizontal) and Type-II (vertical)) of terracotta based ceramic PMFCs (C-PMFC) are incorporated into the paddy field to recover nutrients, energy, and water ("NEW") resources. The peak voltage generated in Type-I and Type-II C-PMFC was 292.1 mV and 321.7 mV respectively. The polarisation study in the ripening phase of paddy showed a maximum power density of 9.1 mW/m² (type-I) and 16.8 mW/m² (type-II). The volume of catholyte recovered is observed to be dependent on the C-PMFC performance and growth phases of the paddy. In the entire 10 weeks of the experimental period, a total of 451 mL and 943 mL of catholyte was collected at 100Ω load in type-I and type-II, respectively. The collected catholyte is alkaline in nature and maximum catholyte recovery is achieved at the active tillering phase and declined with the advancement of the development stages of the plant. Osmotic and electro-osmotic migration of various nutrients like ammonium from the paddy field to cathode chamber of C-PMFC is observed throughout the experiment.